2007
DOI: 10.1007/s10295-007-0266-9
|View full text |Cite
|
Sign up to set email alerts
|

Cutinase production by Fusarium oxysporum in liquid medium using central composite design

Abstract: The objective of the present study was to measure the production of cutinase by Fusarium oxysporum in the presence of several carbon and nitrogen sources (glycides, fatty acids and oils, and several organic and inorganic nitrogen sources), trying to find a cost-effective substitute for cutin in the culture medium as an inducer of cutinase production. The results were evaluated by the Tukey test, and flaxseed oil was found to give the best results as a cutinase inducer. The authors optimized the composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The products were found to be identical, indicating that these four cutinases have the same cutinolytic activity. In previous work, it has been shown that the major components released by enzymatic hydrolysis of cutin are 9,10,8-trihydroxy-C 18 , 10,16-dihydroxy-C 16 , and -hydroxy-C 16 and C 18 with R f values of 0.34, 0.51, and 0.72, respectively (39,50). Three of the spots visible in Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The products were found to be identical, indicating that these four cutinases have the same cutinolytic activity. In previous work, it has been shown that the major components released by enzymatic hydrolysis of cutin are 9,10,8-trihydroxy-C 18 , 10,16-dihydroxy-C 16 , and -hydroxy-C 16 and C 18 with R f values of 0.34, 0.51, and 0.72, respectively (39,50). Three of the spots visible in Fig.…”
Section: Discussionmentioning
confidence: 85%
“…The first cutinases were found in fungi of the genus Fusarium (16)(17)(18)(19)(20). Recently, a low-molecular-mass cutinase from the fungus Thielavia terrestris that is able to efficiently hydrolyze polyesters has been reported by Yang et al (5).…”
mentioning
confidence: 99%
“…The optimization of cutinase production from these wild-type strains has been widely studied in the past decades. Reports have shown that the yield of cutinase is influenced by both the composition of the medium and culture conditions [8][9][10][11]. Certain additives, including cutin, cutin hydrolysis monomers, and some lipids can be used as inducers to improve the production of cutinase [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several strategies such as strain development, culture condition optimization, and mathematical modeling have been widely used. For a certain biotechnological process, developing an appropriate culture medium is of crucial importance because the culture medium can significantly affect product yield [23]. The traditional method of optimization involves varying one factor at a time, while keeping the other constant.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, fractional factorial design and response surface analysis are important tools to determine optimal process conditions. The statistics-based experimental designs for optimization have been used in many areas of biotechnology such July, 2010 as optimization of a culture medium [23], enzyme production [11], ethanol production [24], and biomass production [25].…”
Section: Introductionmentioning
confidence: 99%